Patty's Journey : From Orphanage To Adoption And Reunion - Norling, Donna Scott (Book collections on Project MUSE., 1996)
This inspirational story of one girls search for a home is an engaging first-person narrative of life during the Great Depression and World War II. Readers and critics alike offer lavish praise for Norlings graceful prose and the redemptive tale she shares.